Biomaterials Functionalized with MSC Secreted Extracellular Vesicles and Soluble Factors for Tissue Regeneration. (11th March 2020) - Brennan, Meadhbh Á.; Layrolle, Pierre; Mooney, David J.
Abstract: The therapeutic benefits of mesenchymal stromal cell (MSC) transplantation are attributed to their secreted factors, including extracellular vesicles (EVs) and soluble factors. The potential of employing the MSC secretome as an alternative acellular approach to cell therapy is being investigated in various tissue injury indications, but EVs administered via bolus injections are rapidly sequestered and cleared. However, biomaterials offer delivery platforms to enhance EV retention rates and healing efficacy. This review highlights the mechanisms underpinning the therapeutic effects of MSC‐EVs and soluble factors as effectors of immunomodulation and tissue regeneration, conferred primarily via their nucleic acid and protein contents. Discussed is how manipulating the cell culture microenvironment or genetic modification of MSCs can further augment the potency of their secretions. The most recent advances in the development of EV‐functionalized biomaterials that mediate enhanced angiogenesis and cell survival, while attenuating inflammation and fibrosis, are presented. Finally, some technical challenges to be considered for the clinical translation of biomaterials carrying MSC‐secreted bioactive cargo are discussed. Abstract : The regenerative potential of extracellular vesicles and soluble factors secreted by mesenchymal stem/stromal cells (MSCs) is reviewed. The role of the cell culture environment in modulating the functionality of these secretions, and how biomaterials are harnessed to deliver the MSC secretome in a targeted and controlled manner are highlighted.